Hubungan Antara Kerapatan Mangrove Dengan Kualitas Air Sumur di Desa Gebang Teluk Pandan Kecamatan Pesawaran Provinsi Lampung - Rani Ismiarti Ergantara; Panisean Nasoetion; Munira (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
One of the ecological roles of mangroves is to act as a barrier to seawater intrusion, which is crucial for maintaining the balance of coastal ecosystems. Gebang Village is a coastal area with mangrove forests along its coastline, but the density of these forests varies from location to location. This study aims to determine the relationship between mangrove forest density and the quality of well water in Gebang Village, the main source of clean water for the local community. Well water samples were taken at three locations selected using a purposive sampling technique based on mangrove density levels (low, medium and high) to ensure comprehensive representation. The results showed a significant relationship between mangrove density and salinity, turbidity and total dissolved solids (TDS) in the well water of Gebang Village residents, particularly in wells close to the coastline. The higher the mangrove density, the lower the salinity, turbidity and TDS parameter values in well water, indicating the effectiveness of mangroves in filtering and protecting groundwater sources from seawater contamination.